Academic skills problems workbook - Shapiro, Edward S. 1951- (New York : Guilford, 2004)
A companion to Academic Skills Problems, fourth edition, this workbook provides practice exercises and reproducible forms for use in direct assessment and intervention. Updated to reflect the changes in the fourth edition of the text, the workbook includes teacher and student interview forms, a complete guide to using the Behavioral Observation of Students in Schools (BOSS), tools to support RTI, and exercises in administering assessments and scoring, interpreting, and graphing the results. --from publisher description
Assessing the academic environment. Teacher interview -- Academic performance rating scale -- Student interview -- Direct observation: manual for the Behavioral Observation of Students in Schools (BOSS) -- Assessing instructional placement. Reading -- Math -- Spelling -- Written language -- Summary form for academic assessment -- Instructional modification. The folding-in technique -- Cover-copy-compare -- Progress monitoring. Graphing data -- Developing local norms -- Using goal charts -- Tools for response to intervention: data-based decision making.
Includes bibliographical references(p. 189-190).
Keywords: Remedial teaching; Basic education; Educational tests and measurements